Diagnostic value of single complete compression ultrasonography in pregnant and postpartum women with suspected deep vein thrombosis: prospective study. (24th April 2012) - Le Gal, Grégoire; Kercret, Geneviève; Ben Yahmed, Khalil; Bressollette, Luc; Robert-Ebadi, Helia; Riberdy, Louise; Louis, Patrick; Delluc, Aurélien; Labalette, Marie-Luce; Baba-Ahmed, Mohamed; Bounameaux, Henri; Mottier, Dominique; et al.
Abstract : Objective To assess the safety of using single complete compression ultrasonography in pregnant and postpartum women to rule out deep vein thrombosis. Design Prospective outcome study. Setting Two tertiary care centres and 18 private practices specialising in vascular medicine in France and Switzerland. Participants 226 pregnant and postpartum women referred for suspected deep vein thrombosis. Methods A single proximal and distal compression ultrasonography was performed. All women with a negative complete compression ultrasonography result did not receive anticoagulant therapy and were followed up for a three month period. Main outcome measures Symptoms of venous thromboembolism, second compression ultrasonography or chest imaging, a thromboembolic event, and anticoagulant treatment. Results 16 women were excluded, mainly because of associated suspected pulmonary embolism. Deep vein thrombosis was diagnosed in 22 out of the 210 included women (10.5%). 10 patients received full dose anticoagulation despite a negative test result during follow-up. Of the 177 patients without deep vein thrombosis and who did not receive full dose anticoagulant therapy, two (1.1%, 95% confidence interval 0.3% to 4.0%) had an objectively confirmed deep vein thrombosis during follow-up. Conclusions The rate of venous thromboembolic events after single complete compression ultrasonography in pregnant and postpartum women seems to be within the range of that observed in studies in the non-pregnant population. These data suggest that a negative single complete compression ultrasonography result may safely exclude the diagnosis of deep vein thrombosis in this setting. Trial registration clinicaltrials.gov NCT00740454 .